2021
DOI: 10.20448/journal.522.2021.73.179.188
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Writing in EFL Classroom: Comparison on Group, Pair, and Individual Writing Activities in Argumentative Tasks

Abstract: This study focused on comparing the effects on 32 students’ argumentative writing qualities when they worked alone or collaborated in pairs and groups and explored the students’ opinions towards critical thinking across different writing activities. The 32 students were divided into groups of four (n=8), pairs (n=16) and individuals (n=32). Their papers were rated in terms of content, language use, and organization by three raters. The research employed argumentative writing rubrics, semi-structured interview,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Collaborative writing activities have been found to enhance argumentative writing quality, as they encourage pooling of knowledge, brainstorming, discussing, and problem-solving when writing collaboratively (Moonma & Kaweera, 2021) Writing with instructional strategies affected the academic writing in the context of second language (Silva, 2015). The results of this study prove that the treatment performed in this study has successfully improved the argumentative writing skills as shown by significant increases.…”
Section: Discussionmentioning
confidence: 52%
“…Collaborative writing activities have been found to enhance argumentative writing quality, as they encourage pooling of knowledge, brainstorming, discussing, and problem-solving when writing collaboratively (Moonma & Kaweera, 2021) Writing with instructional strategies affected the academic writing in the context of second language (Silva, 2015). The results of this study prove that the treatment performed in this study has successfully improved the argumentative writing skills as shown by significant increases.…”
Section: Discussionmentioning
confidence: 52%
“…In a 92 Iranian college students survey, Moonma and Kaweera (2021) found some interesting results. Thirty-two students made up the control group and wrote essays alone, whereas sixty students made up the experimental group and wrote essays together.…”
Section: Literature Reviewsmentioning
confidence: 98%
“…Experimental studies (Shehadeh, 2011; Khatib & Meihami, 2015) have found collaborative writing interventions have a significant effect on EFL students’ ideas. Moonma and Kaweera (2021) found that collaborative writing could improve ideas of novice, intermediate and advanced EFL writers. While collaboration can be an effective means of generating ideas, it can be challenging to find a suitable collaborator with whom students can generate ideas in and out of the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%